Relationship of cell-free urine MicroRNA with lupus nephritis in children. Issue 1 (December 2016) - Abulaban, Khalid; Fall, Ndate; Nunna, Ravi; Ying, Jun; Devarajan, Prasad; Grom, Alexi; Bennett, Michael; Ardoin, Stacy; Brunner, Hermine
Abstract Background MicroRNAs (miRNAs) are involved in the post-transcriptional regulation of genes. The objective of this study was to investigate whether select urinary cell-free microRNA's may serve as biomarkers in children with active lupus nephritis (LN) and to assess their relationship to the recently identified combinatorial urine biomarkers, a.k.a. the LN-Panel (neutrophil gelatinase associated lipocalin, monocyte chemotactic protein 1, transferrin, and beta-trace protein). Methods miRNAs (125a, 127, 146a, 150 and 155) were measured using real-time polymerase chain reaction in the urine pellet (PEL) and supernatant (SUP) in 14 patients with active LN, 10 patients with active extra-renal lupus, and 10 controls. The concentrations of the LN-Panel biomarkers (neutrophil gelatinase associated lipocalin, monocyte chemotactic protein-1, transferrin, beta-trace protein) was assayed. Traditional laboratory and clinical measures of LN and lupus (complements, protein to creatinine ratio; Systemic Lupus Erythematosus Disease Activity Index) were also measured. Results All tested miRNAs in the SUP, but not the PEL, were associated with the LN-Panel biomarkers (0.3 < |rPearson | < 0.73;p  < 0.05), miRNA125a, miRNA127, miRNA146a also with C3 and dsDNA antibody levels (|rPearson | > 0.24;p  < 0.05), and miRNA146a with the renal domain of the SLEDAI (|rPearson | = 0.32;p  < 0.05). Mean miRNA levels of patients with active LN did not statistically (P  > 0.05) differ from those of SLE patients without LN or controls. Conclusion Levels of cell-free miR-125a, miR-150, and miR-155 in the urine supernatant are associated with the expression of LN-Panel biomarkers and some LN measures. These miRNA's may complement, but are unlikely superior to the LN-Panel for estimating concurrent LN activity.